ANALISIS HASIL TANGKAPAN IKAN TONGKOL YANG DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA AMBON - Ricardo Siringoringo; Agustinus Tupamahu; Ruslan H. S. Tawari (Universitas Pattimura, 2024)
This research aims to analyze the catches of tuna landed at the Ambon Nusantara Fisheries Port. The research was conducted for two months, from January to February 2023, using descriptive methods. Primary data was collected through direct observation and interviews with fishermen and port officers, while secondary data was obtained from PPN Ambon. The results of this research show that the catch was landed by four fishing fleets, namely purse seines, gill nets, fish trawls and lines fishing. The total catch landed during the 2012-2021 period was 510,203 tons, which was dominated by Auxis thazard. Purse seines are the most dominant fishing gear used, contributing 52.1% of the total catch with a total fishing effort of 597 trips. The productivity of the fishing fleet fluctuates from year to year, the lowest productivity for Euthynnus affinis occurred in 2018 and the highest in 2013, while the lowest productivity forl Auxis thazard occurred in 2017 and the highest in 2018. Fluctuating and low productivity indicates the existence of potential for overfishing. This research suggests the need for further analysis regarding the potential and level of utilization of the two species of frigate tuna landed in PPN Ambon